Hoverlight - "Richardson, Faith." ("Wheaton, Ill. :")
"""A sequel to Dark is a color""--P. 4 of cover. In 2463 teenager Caro learns to deal with her own fear of the past and future through a series of adventures on the planet Clytie."
Keywords: SCIENCE FICTION